Beyond of Business Correspondence - Sri Yanthy Yosepha (JURNAL MITRA MANAJEMEN, 2015)
Abstract Business letter is very important thing that all people do in business. Especially,business man or entrepreneur must know the kind of business letters and how to writebusiness letter for their business.Letter-writing is an essential part of business. In spite of telephone, telex andtelegraphic communication the writing of letters continues, in fact most telephoned andtelegraphed communication have to be confirmed in writing. The paper is done to write of kind of business letters such Introduction letter,Appointment letter and Offer letter, so also discussed about how to write the businessletter and layout of letter.